The Effect of Work-Life Balance on Job Satisfaction through Work Stress with Perceived Organizational Support as a Moderation Variable in Employees of PT Pegadaian Maros Regency - Amal Amal; Suljumansah Suljumansah; Muh Rusli; Mahmud mahmud (STIE Amkop Makassar, 2026)
Abstract This study aims to examine the effect of work-life balance on job satisfaction, with work stress as a mediating variable and perceived organizational support (POS) as a moderating variable. The research adopts a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to analyze the relationships among variables. Data were collected from employees of PT Pegadaian in Maros Regency through a structured questionnaire. The results reveal that work-life balance has a significant negative effect on work stress and a positive effect on job satisfaction. Furthermore, work stress significantly and negatively influences job satisfaction, indicating that higher stress levels reduce employees’ satisfaction. Mediation analysis demonstrates that work stress partially mediates the relationship between work-life balance and job satisfaction, suggesting that work-life balance enhances job satisfaction both directly and indirectly through stress reduction. In addition, perceived organizational support is found to significantly moderate the relationships in the model. Specifically, POS weakens the negative impact of work stress on job satisfaction and strengthens the negative relationship between work-life balance and work stress. The study contributes to the literature by integrating Job Demands-Resources (JD-R) Theory and Social Exchange Theory in a moderated mediation framework, providing a more comprehensive understanding of how organizational and psychological factors interact to influence employee outcomes. Practically, the findings highlight the importance of promoting work-life balance and strengthening organizational support to reduce work stress and improve job satisfaction, particularly in the financial service sector. Keywords: work-life balance, work stress, job satisfaction, perceived organizational support